Two Attempts, Two Ways - Abdul Mohsin Rejaludin, Abdul Hafeez Asyraf; Abd Mutalib, Nor Shahida; Abdull Rasid, Nurul Syeha; Saad, Sakina (International Journal of Human and Health Sciences (IJHHS), 2022)
The COVID-19 pandemic is a global challenge, in terms of physical consequences and mental health catastrophe. Segregation during the quarantine period may serve as a strong motivation for a person to inflict self-destructing acts. A case report of a young man with two attempts of suicide in two different methods was presented. The highlights of this case are the importance of family support and encouraging people to help each other in difficulties regardless of race and religion. A 38-year-old gentleman, an ex-IVDU and a known case of HIV and Hepatitis C, was referred to the otorhinolaryngology (ORL) team following open tracheal injury secondary to a suicidal attempt in August 2021. The airway was successfully secured with an endotracheal tube placed through the exposed airway at the emergency department. Imaging studies showed extensive tracheal injury, segmented fracture of the lower half of cricoid cartilage and crashed fracture of multiple upper tracheal rings with intact trachealis muscle. Isthmus of the thyroid gland and infrahyoid muscles were also cut. Miraculously, there was no vascular and oesophageal injury. Neck exploration, reconstruction of tracheal and tracheostomy were performed immediately under general anaesthesia. It was learned that this was his second suicidal attempt. His first attempt, just one month prior, was driven by low mood, loneliness and feeling helpless during the quarantine period, due to close contact with a positive COVID-19 person. He cut both wrists using a sharp knife and sustained tendon injury that required repair under general anaesthesia. He was then diagnosed with major depressive disorder. Unfortunately, he contracted COVID-19 infection (CAT 2) during the admission. He had no suicidal ideation during hospitalisation, and was subsequently discharged well. Sadly a few weeks later, he was found at his neighbourhood lying unconscious with bleeding from the open neck wound. Once a suicidal attempt was made, the second one is more easily triggered, and the act will be more severe as stated by Beck’s Theory. As for this case, the second attempt is causing very severe injury which nearly cost his life. The patient’s mental health and wellbeing were relentlessly affected as such that he refused to talk about the real event. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S16